Sustainability of the Free Nutritional Meal Program (MBG): An Analysis of the Effectiveness of the Quadruple Helix Model - Hariashari Rahim; Sawedi Muhammad; Suryanto Suryanto; Andi Nurlela; Hidayah Muallim (Universitas Medan Area, 2025)
This article aims to analyze the effectiveness of the Quadruple Helix model in supporting the sustainability of the Free Nutritional Meal Program (MBG) in Makassar City. The problem focuses on the dynamics of collaboration between government, academics, business actors (SPPG and Partners), and community leaders/NGOs in program implementation. To approach this problem, the theoretical reference used is Carayannis and Campbell (2009) on the Quadruple Helix model as a framework for social innovation collaboration. Data were collected through in-depth interviews, observations, and document studies with eight key informants, then analyzed qualitatively using a case study approach. The results show that the city government plays a dominant role as a driver, SPPG and effective partners in the technical realm of food distribution, while academics and NGOs have not been optimally involved, resulting in weak contributions to policy evaluation, nutritional standards, and social support. Obstacles that emerged include limited inter-agency coordination, kitchen capacity, menu variety, and low transparency and community participation. This study concludes that the effectiveness of MBG is still partial, but opportunities for improvement are open through the establishment of a cross-actor coordination body, formal involvement of academics, and strengthening the participation of MSMEs and civil society to ensure the sustainability and quality of the program. This research contributes to enriching the discourse on Quadruple Helix-based social policy collaboration at the local level and provides practical effectiveness in empowering the governance of national nutrition programs based on multi-actor partnerships.